Adverse reactions of vancomycin in humans: A protocol for meta-analysis. Issue 38 (18th September 2020) - Peng, Yang; Li, Chen-yang; Yang, Zhi-ling; Shi, Wei
Abstract: Background: Vancomycin is effective against Gram-positive bacteria and considered as a last resort in the case of ineffective use of other antigens. While due to the occurrence of adverse reactions, the application of vancomycin is strictly limited. We will conduct a meta-analysis to summarize adverse reactions of vancomycin in humans. Methods: To collect comprehensive randomized controlled trials (RCTs), the following electronic databases will be searched: PubMed, Embase, Web of Science, Cochrane Library, the China National Knowledge Infrastructure, Chinese Biomedical Literature Database, and China Science and Technology Journal Database. The range of publication time will be from the inception of the database to August 2020 without language limitation. Two reviewers will independently conduct selection of studies, data extraction and management, and assessment of risk of bias. Any disagreement will be resolved by discussion with the third reviewer. Review Manager 5.3 (The Nordic Cochrane Centre, The Cochrane Collaboration) will be used for meta-analysis. The Cochrane risk of bias tool will be used to assess the risk of bias. Results: This study will synthesize the data from the present eligible high quality RCTs to explore the incidence of adverse reactions such as hypersensitivity reactions, nephrotoxicity, ototoxicity, phlebitis, and agranulocytosis. Conclusion: This meta-analysis will provide systematic evidence for adverse reactions of vancomycin in humans. Study registration number: INPLASY202080094